Evolving impacts of COVID-19 vaccination intentions on travel intentions. Issue 11 (10th September 2021) - Gursoy, Dogan; Can, Ali Selcuk; Williams, Nigel; Ekinci, Yuksel
ABSTRACT: This study examines the evolving impacts of COVID-19 vaccination intentions and vaccine hesitancy on travel intentions. The study also examines the sociodemographic factors that can influence willingness to take the vaccine and vaccine hesitancy since achieving herd immunity is critical for social and economic recovery. Data were collected through five surveys from a total of 4, 223 individuals in the USA between February 2021 and May of 2021. The findings of the study indicate that over 70 per cent of the respondents are willing to get vaccinated with a COVID-19 vaccine. Vaccination intention and hesitancy rates have also been stable over time. Early in the vaccination process, vaccination intentions negatively impacted travel intentions, suggesting that individuals who are willing to get the vaccine postponed their travels in the short term, while individuals who do not plan to get the vaccine may not have changed their travel plans as travel restrictions were eased. However, this negative impact disappeared later as the number of vaccinated individuals significantly increased, closing the gap between the two groups. Findings also suggest that sociodemographic factors such as generational age, gender, marital status, education, region, race, religion, occupation influence the COVID-19 vaccination intention and vaccine hesitancy.